Chronic disease comorbidity and associated factors among cancer patients in eastern Ethiopia - Birhanu, Abdi; Shawel Lemma, Michael; Habtamu, Biruk; Wondwossen Worku, Nahom; Kitessa, Monas; Nigusie, Shambel; Ayana, Galana Mamo; Tenaw, Yehenaw; Sete, Selamawit; Merga, Bedasa Taye; Mussa, Ibsa (Frontiers in Oncology, 2024)
Background The occurrence of long-lasting comorbidities makes cancer management and treatment challenging because of their overlapping poor prognosis. However, there are no data that show the burden of these chronic cases in patients with cancer in Ethiopia. Therefore, this study aimed to assess the burden of and the factors associated with chronic disease comorbidity among cancer patients in the eastern part of Ethiopia. Material and methods A cross-sectional study was conducted on 422 patients with cancer admitted to the only cancer treatment center in eastern Ethiopia. A simple random sampling technique was employed to select the study participants. Data were extracted from the patients’ medical records using a checklist. The collected data were entered into the Epi-Data statistical software version 3.1 and then exported to STATA version 17 for analysis. Bivariate and multivariate logistic regressions were used to assess the association between the outcomes and the independent variables. Finally, adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported. The statistical significance of the factors was indicated at a p-value <0.05. Results Of the 422 eligible medical records identified, 419 (99.3%) were included for analysis. A total of 230 (54.8%, 95%CI = 50.0%–59.6%) patients with cancer presented with one or more chronic diseases. Of these comorbidities, anemia, hypertension, and cardiovascular disease were the most common diseases reported. Obesity at admission (AOR = 1.91, 95%CI = 1.10–3.61) had a significant association with the occurrence of comorbidities among patients with cancer. Conclusion and recommendation The overall prevalence of comorbidity among patients with cancer was relatively lower than that reported in previous studies. Being obese was significantly associated with the occurrence of comorbidities. Attention should be given to the burden of chronic comorbidities among patients with cancer through researching, formulating policies, and improving community literacy to manage comorbidities. Thus, interventions for weight reduction and the early detection and treatment of the comorbidities could limit further complications and lower the incidence of other comorbidities.